ANALISIS POTENSI DAYA LISTRIK PADA PLTMH ALIRAN ANAK SUNGAI TUKAD SUNGI MENGGUNAKAN TURBIN CROSSFLOW - Krisna Raharja, I Gede Agus; Indra Partha, Cokorde Gede; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUM, 2024)
This study evaluates the potential electrical power and turbine rotation speed generated from the flow of the Tukad Sungi tributary to be used in a Microhydro Power Plant (PLTMH) using a crossflow turbine. This study calculates the potential electrical power that can be generated and assesses the performance of the turbine rotation speed in producing optimal power. Quantitative data were obtained by measuring water discharge and turbine rotation speed under various load conditions. The results showed that from the potential water discharge of 0.44 m³/s, only 0.026 m³/s was used, producing a hydraulic power of 484.12 watts and a generator output power of 313.227 watts. The turbine rotation showed a decrease when connected to the generator, which affected the overall electrical output of the system. Although the electrical power output was achieved, the efficiency of the system still needs to be improved to meet the planned street lighting energy needs.